Heme Oxygenase-1 as a Modulator of Intestinal Inflammation Development and Progression - Sebastián, Valentina P.; Salazar, Geraldyne A.; Coronado-Arrázola, Irenice; Schultz, Bárbara M.; Vallejos, Omar P.; Berkowitz, Loni; Álvarez-Lobos, Manuel M.; Riedel, Claudia A.; Kalergis, Alexis M.; Bueno, Susan M. (Frontiers in Immunology, 2018)
Heme Oxygenase 1 (HMOX1) is an enzyme that catalyzes the reaction that degrades the heme group contained in several important proteins, such as hemoglobin, myoglobin and cytochrome p450. The enzymatic reaction catalyzed by HMOX1 generates Fe2+, biliverdin and CO. It has been shown that HMOX1 activity and the by-product CO can downmodulate the damaging immune response in several models of intestinal inflammation as a result of pharmacological induction of HMOX1 expression and the administration of non-toxic amounts of CO. Inflammatory Bowel Diseases, which includes Crohn’s Disease (CD) and Ulcerative Colitis (UC), are one of the most studied ailments associated to HMOX1 effects. However, microbiota imbalances and infections are also important factors influencing the occurrence of acute and chronic intestinal inflammation, where HMOX1 activity may play a major role. As part of this article we discuss the immune modulatory capacity of HMOX1 during IBD, as well during the infections and interactions with the microbiota that contribute to this inflammatory disease.